Pengaruh Adversity Quotient terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Nasution, King Abdul Aziz; Siregar, Macharani Adi Putri Siregar (Media Pendidikan Matematika, 2025)
This study examines how adversity quotient affects their mathematical problem-solving skills while also analyzing the extent of its impact at MTs Qur'an Kisaran. This research is quantitative and uses an ex post facto technique involving 35 eighth-grade students as samples determined using cluster random sampling as the sampling procedure. Tests were used as a measure of mathematical problem-solving, and a questionnaire was used as a measure of adversity quotient to obtain research data. Data were analyzed using descriptive and inferential statistical approaches, including simple linear regression. Linearity is confirmed by a significance value of 0.557 > 0.05, indicating a linear relationship between the independent variable and the dependent variable. Adversity quotient has a positive impact on mathematical problem-solving ability, with a significance value of 0.01 < 0.05, according to simple linear regression analysis. The coefficient of determination also shows that the adversity quotient contributes 75.3% variance to students' problem-solving abilities, indicating that it significantly affects the level of students' mathematical problem-solving.